How is the ultrasound in rheumatology used, implemented, and applied in Latin American centers? Results from a multicenter study (2016)
This study aimed to perform an overview of how ultrasound (US) is being used, implemented, and applied in rheumatologic centers in Latin America (LA). A retrospective, multicenter 1-year experience study was undertaken. Eighteen centers from eight countries were involved. The following information were collected: demographic data, indication to perform an US examination, physician that required the examination, and the anatomical region required for the examination. A total of 7167 patients underwent an US examination. The request for US examinations came most frequently from their own institution (5981 (83.45 %)) than from external referral (1186 (16.55 %)). The services that more frequently requested an US examination were rheumatology 5154 (71.91 %), followed by orthopedic 1016 (14.18 %), and rehabilitation 375 (5.23 %). The most frequently scanned area was the shoulder in 1908 cases (26.62 %), followed by hand 1754 (24.47 %), knee 1518 (21.18 %), ankle 574 (8.01 %), and wrist 394 (5.50 %). Osteoarthritis was the most common disease assessed (2279 patients (31.8 %)), followed by rheumatoid arthritis (2125 patients (29.65 %)), psoriatic arthritis (869 patients (12.1 %)), painful shoulder syndrome (545 (7.6 %)), connective tissue disorders (systemic sclerosis 339 (4.7 %), polymyositis/dermatomyositis 107 (1.4 %), Sjögren’s syndrome 60 (0.8 %), and systemic lupus erythematosus 57 (0.8 %)). US evaluation was more frequently requested for diagnostic purposes (3981 (55.5 %)) compared to follow-up studies (2649 (36.9 %)), research protocols (339 (4.73 %)), and invasive guided procedures (198 (2.76 %)). US registered increasing applications in rheumatology and highlighted its positive impact in daily clinical practice. US increases the accuracy of the musculoskeletal clinical examination, influence the diagnosis, and the disease management. © 2016, International League of Associations for Rheumatology (ILAR).